Dynamics of the US and Southeast Asian relationship : the failure to engage multilaterally. - Lim, Pow Hong. (2008)
In recent years, ASEAN complaints about US preference for bilateralism over multilateralism have been increasing in intensity in the new era of regionalism within Asia. China's "charm offensive" in Southeast Asia has begun to show up the US and US foreign policy in Southeast Asia is seen as being increasingly out of sync and behind times. Thus, this paper seeks to explain why the US is reluctant to engage Southeast Asia multilaterally. An eclectic approach will be used, instead of a single theoretical framework, so as to be able to adequately analyze and understand the complexity of the situation in Southeast Asia.